K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

31 tháng 8 2018

A= \(\frac{25^3.5^3}{6.5^{10}}\)\(\frac{\left(5^2\right)^3.5^3}{6.5^{10}}\)\(\frac{5^6.5^3}{6.5^{10}}\)\(\frac{5^9}{6.5^{10}}\)\(\frac{5}{6}\)

B = \(\frac{2^5.6^3}{8^2.9^2}\)\(\frac{2^5.\left(2.3\right)^3}{\left(2^3\right)^2.\left(3^2\right)^2}\)=\(\frac{2^5.2^3.3^3}{2^6.3^4}\)\(\frac{2^8.3^3}{2^6.3^4}\)\(\frac{2^2}{3}\)\(\frac{4}{3}\)

C = \(\frac{15^3+5.15^2-5^3}{18^3+6.18^2-6^3}\)\(\frac{5^3.3^3+5.5^2.3^2-5^3}{6^3.3^3+6.6^2.3^2-6^3}\)\(\frac{5^3+5^3.3^2-5^3}{6^3.3^3+6^3.3^2-6^3}\)\(\frac{5^3.\left(1+3^2-1\right)}{6^3.\left(3^3+3^2-1\right)}\)\(\frac{5^3.9}{6^3.35}\)    

                                                                                                                                                                                        =\(\frac{5^3.3^2}{2^3.3^3.7.5}\)

                                                                                                                                                                                       = \(\frac{25}{168}\)

D = \(\frac{\left(7^4-7^3\right)^2}{49^3}\)\(\frac{[7^3\left(7-1\right)]^2}{\left(7^2\right)^3}\)\(\frac{7^6.6^2}{7^6}\)\(36\)

6 tháng 8 2016

1)

a. \(\left(3x^2-50\right)^2=5^4\)

\(\Leftrightarrow3x^4-50=625\)

\(\Leftrightarrow3x^4=675\)

\(\Leftrightarrow x^4=225\)

\(\Leftrightarrow x=\sqrt{15}\) 

2)

a. \(\frac{\left(3^4-3^3\right)^4}{27^3}=\frac{3^{16}-3^{12}}{\left(3^3\right)^3}=\frac{3^{12}.3^4-3^{12}}{3^9}=\frac{3^{12}\left(3^4-1\right)}{3^9}\)

\(=\frac{3^{12}.80}{3^9}=3^3.80=27.80=2160\)

b. \(\frac{25^3}{\left(5^5-5^3\right)^2}=\frac{\left(5^2\right)^3}{5^{10}-5^6}=\frac{5^6}{5^6.5^4-5^6}=\frac{5^6}{5^6\left(5^4-1\right)}\)

\(=\frac{5^6}{5^6.624}=\frac{1}{624}\)

10 tháng 9 2020

Ta có: \(\frac{4^2.25^2+32.5^3}{2^3.5^2}=\frac{2^4.5^4+2^5.5^3}{2^3.5^2}\)

                                           \(=\frac{2^4.5^3.\left(5+2\right)}{2^3.5^2}\)

                                           \(=2.5.7\)

                                           \(=70\)

10 tháng 9 2020

\(\frac{4^2.25^2+32.5^3}{2^3.5^2}=\frac{\left(2^2\right)^2.\left(5^2\right)^2+2^5.5^3}{2^3.5^2}=\frac{2^4.5^4+2^5.5^3}{2^3.5^2}=\frac{2^4.5^3\left(5+2\right)}{2^3.5^2}\)

= 2.5.7 = 70